2023
DOI: 10.5194/egusphere-egu23-5900
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Solar total radiation input and terrestrial temperature in the two millennia of 600-2

Abstract: <p>The<span class="Apple-converted-space">  </span>long-term millennial oscillations of the baseline<span class="Apple-converted-space">  </span>solar background magnetic field (SBMF) and the ephemeris of<span class="Apple-converted-space">  </span>the Sun-Earth distances are compared with the oscillations of solar irradia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…We explored the two sets of the terrestrial temperature variations obtained since 1850 using the wavelet analysis and detected in the GLB datasets a clear period of 21.4 and 36 years, while in the Had-CRUTS dataset only weaker indication of the period of about 19.6 years. This 21.4 y period is clearly associated with the variations of solar activity defined by the eigenvectors of the solar background magnetic field (SBMF) [52,53]. A similar period of 21.4 years was also reported previously in the frequency of volcanic eruptions [69].…”
Section: Discussionsupporting
confidence: 77%
See 3 more Smart Citations
“…We explored the two sets of the terrestrial temperature variations obtained since 1850 using the wavelet analysis and detected in the GLB datasets a clear period of 21.4 and 36 years, while in the Had-CRUTS dataset only weaker indication of the period of about 19.6 years. This 21.4 y period is clearly associated with the variations of solar activity defined by the eigenvectors of the solar background magnetic field (SBMF) [52,53]. A similar period of 21.4 years was also reported previously in the frequency of volcanic eruptions [69].…”
Section: Discussionsupporting
confidence: 77%
“…The wavelet analysis of ice area coverage in Arctic shows (Figure 7) for the Arctic ice (top plot) and Antarctica ice (bottom plot). It can be observed that the Arctic ice areas change periodically with a period of 10.7 years that is the averaged period of solar activity defined by the averaged sunspot numbers [52,53]. While Antarctica's ice areas do not reveal this link with the solar activity showing some periods of 5.6 and 15.6 years within the 95% confidence level, possibly, affected by some local events.…”
Section: Spectral Features Of the Ice Coversmentioning
confidence: 96%
See 2 more Smart Citations
“…Initial strides have also been made in reconstructing solar total and spectral irradiance values over millennia. Valentina Zharkova et al [3] conducted a comprehensive exploration of the periodicities of solar activity and radiation, reaching back centuries and millennia. This research incorporates the data from various sources, including the Holocene data of solar irradiance derived from the abundance of the 14C isotope.…”
Section: Introductionmentioning
confidence: 99%